Financial sector in resource-dependent economies - Sanna Kurronen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
This paper examines financial sector characteristics in resource-dependent economies. Using a unique dataset covering 133 countries, we present empirical evidence that the banking sector tends to be smaller in resource-dependent economies, even when controlling for several other factors which have been shown to have a significant effect on financial sector development in previous studies. Moreover, the threshold level at which the increasing resource-dependence begins to be harmful for domestic banking sector is very low. We also find evidence that the use of market-based and foreign financing is more common in resource-dependent economies. Further, we argue that a relatively small financial sector used to cater the needs of the resource sector might be unfavorable for emerging businesses, thereby hampering economic diversification and reinforcing the resource curse. resource dependence, resource curse, financial sector, banks, panel data, G20, O16, O57, Q32
URN:NBN:fi:bof-201408072047
Keywords: G20; O16; O57; Q32; 330